The Effect of Exercise Intensity on Sweat Rate and Sweat Sodium and Potassium Losses in Trained Endurance Athletes - Holmes, Nicola; Bates, Graham; Zhao, Yun; Sherriff, Jill; Miller, Veronica (2016)
This randomized crossover trial study was designed to investigate the relationship between exercise intensity, sweat rate and sweat sodium and potassium concentrations of trained endurance athletes in order to determine sodium and potassium losses and therefore requirements. Eighteen male endurance athletes (age 37.9±9.7 y, weight 83.2±13.6 kg, VO2 max 60.8±9.4 mL/kg.min-1) were randomized into one of three groups for the experimental trials. Group L began with the low intensity trial (60%HRmax), group M with the moderate intensity trial (80%HRmax) and group H with the high intensity trial (time trial). Over three consecutive weeks, all participants performed each of the three trials. There was a significant increase in average sweat sodium (p<0.01) but not potassium concentration between the L and H exercise trials (L=30.6 mmol/L±11.4, H = 49.4 mmol/L±22.9). Inter-individual coefficient of variance for average sodium concentrations ranged from 37-47%. There was a significant positive linear relationship (p<0.001) between sweat rate (L/h) and sweat sodium concentration (mmol/L) (r2 = 0.229). These measurements computed to significant increases in both sodium and potassium losses (mg/h) with increasing exercise intensity. In conclusion, there was considerable individual variation in sweat rate and sodium loss in endurance athletes with losses up to 4.5 g sodium per hour at high intensity. Thus endurance athletes with high sweat rates are at risk for substantial sodium loss and should ensure they choose salty food as well as hydrate adequately after an event.